CHECKING THE ECOLOGICAL SAFETY OF NOKBARG TUYASINGREN PLANT (International journal of artificial intelligence, 2024)
The plant Nokbarg tuyasingren (Cynara scolymus) is mainly distributed in the Mediterranean region, but is now widely distributed throughout the world. This plant is known not only for its unique appearance, but also for its importance in the medical and food fields. The Nokbarg tuyasingren plant, along with its multifaceted benefits, is also important from an ecological safety point of view. In this article, it is aimed to investigate the ecological safety of the nokbarg tuyasingren plant and to study its environmental impact.